2009
DOI: 10.1074/jbc.m109.019448
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium-Hydrogen Exchanger NHE1 Is an Akt Substrate Necessary for Actin Filament Reorganization by Growth Factors

Abstract: The kinase Akt mediates signals from growth factor receptors for increased cell proliferation, survival, and migration, which contribute to the positive effects of Akt in cancer progression. Substrates are generally inhibited when phosphorylated by Akt; however, we show phosphorylation of the plasma membrane sodium-hydrogen exchanger NHE1 by Akt increases exchanger activity (H ؉ efflux). Our data fulfill criteria for NHE1 being a bona fide Akt substrate, including direct phosphorylation in vitro, using mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 69 publications
(87 reference statements)
6
98
3
1
Order By: Relevance
“…AKT phosphorylation of NHE1 is stimulatory, induces cytoskeletal remodeling, and is necessary for the activation of NHE1 by insulin and PDGF [59]. We confirmed that AKT interacts with NHE1 in MDA-MB-231 cells by co-immunoprecipitation experiments (Fig.…”
Section: Nhe1 and Signal Transduction Proteinssupporting
confidence: 73%
“…AKT phosphorylation of NHE1 is stimulatory, induces cytoskeletal remodeling, and is necessary for the activation of NHE1 by insulin and PDGF [59]. We confirmed that AKT interacts with NHE1 in MDA-MB-231 cells by co-immunoprecipitation experiments (Fig.…”
Section: Nhe1 and Signal Transduction Proteinssupporting
confidence: 73%
“…Examples of kinase-mediated activators of NHE1 include: extracellular signal regulated kinases ERK1/2 which are important in the activation of NHE1 in response to intracellular acidosis, and for which NHE1 serves as a signal scaffold (54,55); AKT (protein kinase B) which activates NHE1 in response to insulin and platelet-derived growth factor in fibroblasts (56), but inhibits NHE1 activity in cardiomyocytes (57); -Raf which phosphorylates NHE1 at amino acid threonine 653 (58); and p90 ribosomal S6 kinase (p90 RSK ) which phosphorylates NHE1 at serine 703, activating the exchanger in response to serum (59). Adaptor protein 14-3-3 binds NHE1 at the phosphorylated serine 703 residue and prevents its dephosphorylation (60).…”
Section: Nhe1: the Major Cellular Regulator Of Ph Homeostasismentioning
confidence: 99%
“…Changes in the rate of pHi recovery can be used to determine the regulation of ion transporter activity, including by growth factors, oncogenes, and extracellular osmolarity. For example, platelet-derived growth factor increases the activity of the plasma membrane Na + /H + exchanger NHE1, as determined by increased pHi recoveries measured in a nominally HCO 3 À -free HEPES buffer that prevents the activity of anion exchangers (Meima, Webb, Witkowska, & Barber, 2009). Fluorescence intensities are used to determine ratios that are converted to pH values using a nigericin calibration.…”
Section: Ph-sensitive Ratiometric Dyesmentioning
confidence: 99%